2016
DOI: 10.1186/s40064-016-3253-7
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance operon emrAB contributes for chromate and ampicillin co-resistance in a Staphylococcus strain isolated from refinery polluted river bank

Abstract: EmrAB operon is known for multidrug resistance in bacteria and yet has not been reported related to heavy metal resistance or antibiotics/heavy metal co-resistance. Strain Staphylococcus aureus LZ-01 which was isolated from industrial wastewater discharging site can co-resist to 6 mM Cr(VI) and 0.75 mg/ml ampicillin. Transcriptome data showed that an emrAB operon was upregulated (1.29-folds for emrA, 2.14-folds for emrB) under 0.4 mM Cr(VI) treatment. Quantitative PCR results revealed that this operon was upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…400,401 Further, the multidrug efflux system EmrAB from S. aureus has been shown to act upon chromium(VI). 402 Overall, these observations emphasize that the promiscuity of efflux systems can include the ability to translocate substrates that are very different in steric bulk and potentially charge distribution. They also support a role for metal ions in maintaining the expression of an efflux system even in the absence of its antimicrobial substrate(s).…”
Section: Resistance To Heavy Metalsmentioning
confidence: 92%
“…400,401 Further, the multidrug efflux system EmrAB from S. aureus has been shown to act upon chromium(VI). 402 Overall, these observations emphasize that the promiscuity of efflux systems can include the ability to translocate substrates that are very different in steric bulk and potentially charge distribution. They also support a role for metal ions in maintaining the expression of an efflux system even in the absence of its antimicrobial substrate(s).…”
Section: Resistance To Heavy Metalsmentioning
confidence: 92%
“…A total of 10 rRNA, 61 tRNA, and 2,510 protein-coding genes were predicted by in silico annotation of the genome. Of note, the emr A and emr B genes, implicated in chromate and ampicillin co-resistance in Staphylococcus aureus LZ 01 ( Zhang et al 2016 ), were identified in the genome of SC5. These genes are also observed in the genomes of the other four S. arlettae chromium-resistant strains isolated from the same environment.…”
Section: Resultsmentioning
confidence: 99%
“…Further, evidence of shared genetic tolerance mechanisms for metals and antibiotics was found in Staphylococcus aureus isolated from a polluted riverbank. S. aureus contained a novel emrAB operon encoding efflux pumps that were inducible by the heavy metals Cr(VI) and manganese and the antibiotics ampicillin and chloramphenicol (Zhang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%